KAFA: A novel interoperability open framework to utilize Indonesian electronic identity card - Rolly Maulana Awangga; Nisa Hanum Harani; Muhammad Yusril Helmi Setyawan (Universitas Ahmad Dahlan, 2019)
Indonesian people have electronic citizen card called e-KTP. e-KTP is NFC based technology embedded inside Indonesian citizenship identity card. e-KTP technology has never been used until now since it was launch officially by the government. This research proposes an independent framework for bridging the gap between Indonesia regulation for e-KTP and commercial use in the many commercial or organization sector. The Framework proposes interoperability framework using novel combination component, there are e-KTP reader, Middleware and Web Service. KAFA (e-KTP Middleware and Framework) implementing Internet of Things (IoT) concept to make it as open standard and independent. The framework use federation mode or decentralized data for interoperability, to make sure not breaking the law of privacy. Extended development of AES-CBC cipher algorithm was used to encrypt the data on the transport between middleware and web service.